Acute effects of ethanol on postprandial lipid metabolism - Mohd Esa, Norhaizan; Hawdon, Anne J.; Wright, John W.; Gould, Barry J.; Griffin, Bruce A. (2001)
Enhanced postprandial lipaemia provides an important metabolic stimulus for the production of abnormalities in serum lipoproteins, which increase the risk of coronary heart disease (CHD) (Griffin, 1997). Ethanol elevates the postprandial rise in serum triacylglyceral (TAG) following the ingestion of dietary fat by promoting the production of TAG in the liver which is synthesized and secreted into the circulation as very low density lipoprotein (VLDL) (Connor and Connor, 1998). In contrast, very little is known about the effects of ethanol on TAG associated with dietary chylomicrons (eM). A study was designed to examine the acute effect of ethanol on postprandial TA G-rich lipoproteins (TRL) of intestinal and hepatic origin. and the activity of lipoprotein lipase (LPL), the rate-limiting determinant of TAG remaval. Eight healthy, non-smoking male subjects (25-40 years) were given a test meal containing 52g ofmixed fat on two separate occasions with and without ethanol (0.6g ethanol/kg body weight - 5 units). Blood samples were taken over 8 hours for the determination of total plasma-TAG. cholesterol, apo B, high density lipoprotein (HDL), low density lipoprotein (LDL) and the separation of 'TAG-rich' lipoprotein (TRL) fraction. Post-heparin (7500 U) lipase activity (PHLA) was measured at 8 hours.Ethanol consumption together with the test meal compared to control increased the area under the curve (AUC) for plasma-TAG (P<O.OI), TRL-TAG (P<O.05), TRL-apo B-48 and a decreased PHLA (nonSignificant). Ethanol enhanced the TAG response in the late poslprandial phase (5-8 hours) is consistent with either an increase in the secretion or residence time ofTRL particles. Moreover, the significant elevation in TRL-apo B-48 suggests that eM-remnant also contributed to the ethanol-induced hypertriacylglycerolaemia. The inverse relationship between PHLA and plasma. TAG (P<O.005) furthermore could probably explain the delayed clearance of TRL after ethanol intake. However, no Significant differences were evident for plasma-cholesterol, total apo B and the level of high density lipoprotein (HDL)-cholesterol and low density lipoprotein (LDL)-cholesterol were also not significantly changed. This study demonstrated that the elevated TAG levels in the postprandial state after ethanol consumption is partly due to the accumulation of intestinally derived lipoprotein particles.